Thermal impulse response in porous media for transpiration cooling systems - Hermann, T; McGilvray, M; Ifti, H; Hufgard, F; Löhle, S (American Institute of Aeronautics and Astronautics, 2020)
A solution of the coupled differential equations for fluid and solid phases in a one-dimensional porous medium in thermal nonequilibrium is presented using the concept of analyzing the impulse response. The impulse response is shown to be sensitive to the volumetric heat transfer coefficient and the coolant mass flux. Experimental data obtained from surface heating of transpiration-cooled porous zirconium di-boride (ZrB2) samples are compared to a newly developed theoretical model. The surface and backside temperatures of the solid are measured using thermographic imaging and thermocouple instrumentation. The noninteger system identification approach is used to experimentally obtain the thermal impulse response, which is then compared to the model prediction. Good agreement is found between the simulated and experimental data with average deviations below 10%. The developed model provides the basis for inverse heat transfer measurements and further analysis of transpiration-cooled materials.